2018
DOI: 10.1001/jamanetworkopen.2018.2969
|View full text |Cite
|
Sign up to set email alerts
|

Global Public Attitudes About Clinical Research and Patient Experiences With Clinical Trials

Abstract: This survey study reviews the findings of the attitudes, perceptions, and experiences of clinical trials among clinical trial participants and nonparticipants in 68 countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 16 publications
(12 reference statements)
5
73
0
Order By: Relevance
“…Some evidence shows that research burden can be common in RCTs. For example, half the respondents in an international survey of 2194 clinical trial participants considered trial participation as disruptive to their daily routine [22]. The concept of research burden has featured prominently in recent priority-setting partnerships for trial methodology research [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence shows that research burden can be common in RCTs. For example, half the respondents in an international survey of 2194 clinical trial participants considered trial participation as disruptive to their daily routine [22]. The concept of research burden has featured prominently in recent priority-setting partnerships for trial methodology research [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Time constraint was another reason for declining participation. A previous study showed that time constraint was more of a concern to younger participants due to work commitments [8]. Although the majority of our study population was above 65, this reason was voiced by about one-third of the participants.…”
Section: Discussionmentioning
confidence: 78%
“…As researchers are faced with the problem of patient participation in research globally, understanding the barriers limiting patients' interests in research is important in designing future research projects that ensure participant satisfaction and recruitment. While extensive work has been done to evaluate Western patients' perspectives, there have been only few studies representing Asian patients' attitude towards research participation, which could be due to lack of patient or physician interest as well as limited funding and infrastructure to promote research [8,9], while various Asian studies have been performed to assess attitudes of healthy subjects or mixed group of patients towards research participation [2,6,[10][11][12][13][14]; to the best of our knowledge, this is the first Asian study on Parkinson patients to understand their attitudes towards clinical research and tissue donation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations